Koninginins X-Z, Three New Polyketides from Trichoderma koningiopsis SC-5 - Weiwei Peng; Jianbing Tan; Zihuan Sang; Yuantao Huang; Li Xu; Yuting Zheng; Siyu Qin; Haibo Tan; Zhenxing Zou (Molecules, 2023)
Koninginins X-Z (1–3), three novel polyketides, were isolated from the solid fermentation of the endophytic fungus Trichoderma koningiopsis SC-5. Their structures, including the absolute configurations, were comprehensively characterized by a combination of NMR spectroscopic methods, HRESIMS, 13C NMR, DFT GIAO 13C NMR, and electronic circular dichroism calculations as well as single crystal X-ray diffraction. In addition, all the compounds were evaluated for antifungal activity against Candida albicans.